THE ACHIEVEMENT OF ENGLISH LANGUAGE CURRICULA FOR SECONDARY STAGE FROM THE PERSPECTIVES OF EFL TEACHERS AND SUPERVISORS IN JORDAN - Mohammad Ahmad Bani Amer; Majid Mohammad Al-Khataybeh (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2021)
This study aims to investigate whether or not the goals of English language curricula for secondary stage have been achieved from the perspectives of EFL teachers and supervisors in Jordan. The participants were 101 EFL teachers and 8 supervisors in Al_Karak educational directorates of Education during the first semester 2020/2021. The researchers designed a questionnaire consisting of fifty-nine items in four areas: listening, speaking, reading and writing skills, used to collect the data for this study. The findings of this study showed that English language teachers and supervisors were mostly satisfied with the goals of English language curriculum for secondary stage. The means for all the areas according to English language teachers was 3.31 while the means for all the areas according to English language supervisors was 3.27. This implies that English language teachers and supervisors were satisfied with the goals of English language curriculum for secondary stage.